A painting of us. - Nuraliah Norasid. (2009)
As the common adage goes, a picture speaks a thousand words. A picture, unlike a person, cannot produce sounds on their own. To speak, as in to utter sounds, requires either the right devices or the right anatomy, neither of which a picture has. If someone speaks to you in a language you do not understand, the person is still “speaking” as he or she is able to carry out our common understanding of speaking. It is not so with a picture. A picture only “speaks” if the one who “listens”, understands. Otherwise, the picture remains mute.